2009
DOI: 10.1097/mpg.0b013e31818f0902
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Multichannel Intraluminal Impedance Technique in Infants and Children

Abstract: Recently, multichannel intraluminal impedance (MII) was added to the repertoire of tests available to study esophageal (patho)physiology in children. MII has since been used in 2 major areas. First, it has been used as a diagnostic test for gastroesophageal reflux disease (GERD). The main advantage over traditional pH monitoring is its ability to detect both acid and nonacid gastroesophageal reflux (GER) and to discern between liquid and gas GER.Although feasible with multiple pH sensors, the MII technique rou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(62 citation statements)
references
References 64 publications
3
58
0
1
Order By: Relevance
“…The frequency of GER events observed in the present study was quite similar to that reported by van Wijk et al [20] in neonates with frequent regurgitation as detected by MII-pH monitoring (between 1.6 and 6 GER events per hour). The RI recorded in the present study (4%) is lower than the "abnormal" threshold of 7%…”
Section: Characteristics Of Ger Eventssupporting
confidence: 79%
“…The frequency of GER events observed in the present study was quite similar to that reported by van Wijk et al [20] in neonates with frequent regurgitation as detected by MII-pH monitoring (between 1.6 and 6 GER events per hour). The RI recorded in the present study (4%) is lower than the "abnormal" threshold of 7%…”
Section: Characteristics Of Ger Eventssupporting
confidence: 79%
“…Esophageal multichannel intraluminal impedance is used for the detection of gastroesophageal reflux (GER) episodes in infants, children and adults (1)(2)(3). This is a technique to measure esophageal flow represented by changes in conductivity of adjacent contents between multiple electrode pairs on a catheter (4).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple intraluminal impedance technique is based on the ionic concentrations of the luminal contents 6,10 . Bolus with no ionic contents, such as gas (air), results in a rise in impedance but relatively high ionic contents such as refluxate results in a drop in impedance.…”
Section: Discussionmentioning
confidence: 99%
“…This method detects reflux in the pH below 4, but GER episodes of weak acidity are not detected with this method. Neonates, infants and neurologically impaired children tend to have weak acid reflux because of the frequent feeding and neutralization of the gastric content following milk or formula [6][7][8] . Therefore, it is not possible to detect all reflux episodes with pH monitoring.…”
mentioning
confidence: 99%